Adaptation features of the invasive species Berberis aquifolium Pursh and Daphne laureola L. in forest communities on the Southern Coast of Crimea - N. A. Bagrikova; Z. D. Bondarenko (Труды по прикладной ботанике, генетике и селекции)
Background. Special attention is paid in many regions to invasive plant species introduced into natural plant communities. Studying the degree of naturalization of Berberis aquifolium Pursh and Daphne laureola L. on the Crimean Peninsula is important because these species are currently observed in different types of forest vegetation, including Protected Areas.   Materials and methods. Forest plant communities with B. aquifolium and D. laureola served as the research target. A geobotanical survey was conducted in 2019–2021 using the Braun-Blanquet approach. The JUICE platform and the PC-ORD 5.0 algorithm were employed to perform the cluster analysis, and the PAST 3.26 software for the ordination analysis. Twelve factors were considered: soil humidity (Hd), humidity fluctuation (fH), substrate acidity (Rc), anionic composition (Tr), carbonate content (Ca), nitrogen content (Nt), granulometric (mechanical) composition of the substrate (Ae), illuminance of the community (Lc), thermal regime (Tm), aridity/humidity (Om), cryoregime (Cr), and climate continentality (Kn). Phytoindication technique was used to determine the parameters of ecological niches.   Results and conclusion. The communities with B. aquifolium and D. laureola on the Southern Coast of Crimea were found to belong to the Quercetea pubescentis and Erico-Pinetea classes of vegetation. The species appeared to be most widespread in the pine-oak-hornbeam and oak-hornbeam-dogwood forest communities where they occurred mainly along riverbeds, near springs, and along gully bottoms. According to a majority of edaphoclimatic factors, their habitat conditions corresponded to the parameters of the fundamental niches for the studied species, which explains their high degree of adaptation to the natural environments on the Southern Coast of Crimea.